The effects of implementation intentions on prospective memory in young and older adults - Koo, Yu Wen; Neumann, David L.; Ownsworth, Tamara; Shum, David H. K. (Frontiers in Psychology, 2022)
Prospective memory (PM) is the ability to perform a planned action at a future time, while carrying on with other unrelated tasks. Implementation Intentions (II) is a promising metacognitive strategy for improving PM in older adults, though its generalization and longer-term effects are not well-understood. We examined the effects of II on PM in 48 community-dwelling older adults (77% female, Mage = 71.52) and 59 young adults (75% female, Mage = 19.86). Participants were randomly allocated to a conventional instruction or II group and administered a laboratory-based PM task in the first session. In the second session, participants returned to complete a similar but new laboratory-based PM task and an ecological PM task without prompts to use a strategy. We found strong age effects on PM performance whereby older adults performed worse than young adults across all PM tasks. While the overall facilitation effect of II was not statistically significant, there was a trend that this strategy facilitated PM performance on the laboratory-based PM task in the first session for older adults with a medium sized effect (d = 0.37). The generalization and longer-term effect of II were not significant for either the similar laboratory-based or the ecological PM task. These results suggest that a single-session II intervention may not be sufficient to elicit transfer to other similar new PM tasks in healthy populations.